2018
DOI: 10.1002/jnr.24377
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum VGF protein levels discriminate bipolar depression from major depressive disorder

Abstract: Misdiagnosis between major depressive disorder (MDD) and bipolar depression (BD) is quite common. Our previous study found significantly lower serum VGF (non‐acronymic) in MDD patients. However, it is unclear whether same changes occur in BD patients. Therefore, we aimed to investigate the relationship between serum VGF levels in BD and MDD patients. General information, scores of 17‐item Hamilton Depression Rating Scale (HDRS), and fasting blood samples of all participants including 30 MDD patients, 20 BD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In this context, it is interesting to note that serum VGF levels were significantly lower in patients with major depressive disorder than in bipolar depression (BD) patients, but higher in BD patients compared to healthy control individuals. No correlation was found between serum VGF levels and any data of persons (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…In this context, it is interesting to note that serum VGF levels were significantly lower in patients with major depressive disorder than in bipolar depression (BD) patients, but higher in BD patients compared to healthy control individuals. No correlation was found between serum VGF levels and any data of persons (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…For instance, in patients with the major depressive disorder who were drug-free for at least 2 weeks, VGF mRNA levels in leukocytes were significantly reduced, by approximately 50%, compared to healthy subjects [62]. In another study, VGF levels in serum and prefrontal cortex decreased in patients with the major depressive disorder [63]. In this study, patients with hypothyroidism as a result of AIT and post-operative hypothyroidism VGF expression was reduced, while it was significantly increased in the group of AIT patients with elevated serum autoantibodies, such as anti-Tg and anti-TPO.…”
Section: Discussionmentioning
confidence: 95%
“…Previous blood-based proteomic studies have identified aberrations in several inflammatory markers, neurotrophins, and oxidative stress markers [ 10 ]. Some studies have developed composite biomarker panels aiming at distinguishing between psychiatric disorders [ 7 , 11 15 ] or classifying mood states [ 16 , 17 ]. One study derived a promising biomarker panel for the classification of both pre-diagnostic and misdiagnosed cases with bipolar disorder [ 18 ] but no diagnostic biomarkers have yet been validated for clinical use.…”
Section: Introductionmentioning
confidence: 99%